ANALYSIS AND IMPLEMENTATION OF VIRTUAL LOCAL AREA NETWORK (VLAN) DESIGN USING POX CONTROLLER - Onno Widodo Purbo (INFOKUM, 2020)
The limitations of LAN gave birth to a VLAN technology that allows the configuration of a virtual computer network (virtualization), VLAN is a network model that is not limited to physical locations such as LANs, this results in a network being configured virtually without having to obey the physical location of the equipment, By utilizing various techniques, especially subnetting techniques and the use of better hardware (including switches), the concept of a Virtual Local Area Network (VLAN) emerged which can be maximized compared to a Local Area Network (LAN). In this study, a VLAN network simulation using a Pox controller was carried out so that it could find out the results of the VLAN network evaluation using a Pox controller. The use of VLANs will make network arrangements very flexible where segments can be created depending on the organization or department, regardless of the workstation location, VLANs are also functioned as a method for creating networks that are logically arranged individually, in addition to VLAN techniques. superior to LAN where the average LAN data transmission time is 4 ms longer than VLAN. With this VLAN can create very many LAN segments in an interface. This allows a network to be configured virtually without having to obey the physical location of the equipment.